2015
DOI: 10.3892/etm.2015.2866
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leucine-rich glioma-inactivated 1 limbic encephalitis: A case report and literature review

Abstract: Abstract. This study describes the case of a 41-year-old woman admitted for anterograde memory loss, right facial grimacing and right arm posturing that had begun 1 month previously. Cranial magnetic resonance-diffusion weighted imaging and -fluid-attenuated inversion recovery imaging revealed a hyperintense signal in the left hippocampus and right basal ganglia, but no contrast enhancement. An electroencephalogram revealed rhythmic sharp and slow waves and rhythmic θ build-ups in the left temporal area. Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Anti-LGI1 antibodies are against the VGKC complex and are mostly expressed in the hippocampus (7). Hippocampal involvement was also observed in our patient's MRI.…”
Section: Discussionsupporting
confidence: 61%
“…Anti-LGI1 antibodies are against the VGKC complex and are mostly expressed in the hippocampus (7). Hippocampal involvement was also observed in our patient's MRI.…”
Section: Discussionsupporting
confidence: 61%
“…Abnormal hyperintensities on her brain MRI first appeared in the unilateral right caudate nucleus and putamen (Figure 1A-B), which is a rare feature in this disease as previous reports have shown that abnormalities mainly involved the bilateral limbic system. 6,7 Some previous papers also reported the involvement of basal ganglia in patients with LGI1 antibody-associated limbic encephalitis, 8,9 but in their cases, the patients responded well to the initial methylprednisolone or intravenous immunoglobulin therapy. In our case, the patient was refractory to the initial methylprednisolone pulse therapy and improved after the additional treatments of plasma exchange and intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 97%
“…The autoimmune inflammation can be further categorised on the basis of antibodies against the nuclear antigens (paraneoplastic antibodies), antibodies against the target cell surface antigens (VGKC, NMDA) and those associated with unknown antibody (seronegative limbic encephalitis). 1,6 The VGKCs are situated both in the central nervous system and the peripheral nervous system; and are important regulators of cell action potential. LGI1 and CASPR2 are two of its associated components.…”
mentioning
confidence: 99%
“…German researchers were the first to report the neuropathological characteristics of anti-LGI1 limbic encephalitis and suggested a CD8+ T-cell-mediated immune process directed against hippocampal neurons. 6 Others state that LGI1 antibodies belong to IgG 4 subclass; and postulated mode of action is through direct functional interference. 4 The disease has the characteristics of sub-acute memory and cognitive disturbance, behavioural changes, usually accompanied by seizures.…”
mentioning
confidence: 99%
See 1 more Smart Citation